Synthesis and Flame Retardant Characteristic of Polyphosphazene Nanospheres - Zhao, Zhengping; Zhu, Yanyan; Yu, Fengying (Asian Journal of Chemistry, 2015)
Polyphosphazene (PZs) nanospheres were synthesized by plus template induced self-assembly and added into low-density polyethylene (LDPE) to prepare LDPE/PZs nanocomposites to study its flame retardant characteristic. When 5 wt. % polyphosphazene nanospheres filling, the limiting oxygen index values changed from 17 to 21 and maximum ratio of optical density dropped from 157.86 to 137.46, which indicated that polyphosphazene nanospheres play a swelling flame retardant effect. Mechanical testing of the composites showed that when 1 wt. % fillers, the tensile strength changed from 28.6 to 36.2 MPa and elongation at break increased from 674 to 767 %. polyphosphazene nanospheres could be uniformly dispersed in the low-density polyethylene matrix and played a toughening and enhancing effect due to its crosslinking structure and lots of hydroxide radical on the surface.